Recurrent bilateral superficial vein thrombosis in hereditary hemochromatosis- a case report - Abousherif, Wael; Vameghestahbanati, Motahareh; Hallak, Ahmed (International Journal of Research in Medical Sciences, 2022)
We report a rare case of recurrent bilateral superficial vein thrombosis (SVT) in a 45-year-old former smoking male with hereditary hemochromatosis on anticoagulation therapy with unremarkable hypercoagulable workup. This case report adds to the growing evidence that hemochromatosis is one of the rare causes of recurrent SVT, and thrombosis can still occur despite full-dose anticoagulation. Future studies assessing optimal management of the recurrent SVT in hemochromatosis patients are warranted.